Law Enforcement of Value Added Tax (VAT) Collection of Goods at PT. Duta Jaya Food Binjai Kota Based on Law Number 11 of 1994 - Sitepu, Karolina; Wahyuni, Sri; Siregar, Dahris; Darma, Mospa (Universitas Pahlawan Tuanku Tambusai, 2024)
Taxes which are of various types, are an important component of state revenue. Value added tax is one of its types. Until now, the potential revenue from this value-added tax has not been fully used for the benefit of the state and the people. In the context of this study, taxpayers have to pay input tax, but there are invoices tucked away or missing, which can lead to misreporting VAT. Empirical legal methodology is used in this study. For the purpose of this study, primary and secondary data sets comprising legal materials at all stages of development were used.. Next, the data is evaluated, classified, analyzed, and conclusions are drawn. The aim of this study is to ascertain the limitations and implementation efforts of Law Number 42 of 2009 concerning Value Added Tax on Goods and Services and Sales Tax on Luxury Goods, as well as the manner in which PT. Duta Jaya Food Binjai Kota carries out the law on collecting value added tax (VAT) on goods.